A new biological bone remodeling in silico model combined with advanced discretization methods. (26th March 2019) - Peyroteo, Madalena M. A.; Belinha, Jorge; Dinis, Lucia M.J.S.; Natal Jorge, Renato M.
Abstract: Bone remodeling remains a highly researched topic investigated by many strands of science. The main purpose of this work is formulating a new computational framework for biological simulation, extending the version of the bone remodeling model previously proposed by Komarova. Thus, considering only the biological aspect of the remodeling process, the action of osteoclasts and osteoblasts is taken into account as well as its impact on bone mass. It is conducted a spatiotemporal analysis of a remodeling cycle obtaining a dynamic behavior of bone cells very similar to the biological process already described in the literature. The numerical example used is based on bone images obtained with scanning electron microscopy. During simulation, it is possible to observe the variation of bone's architecture through isomaps. These maps are obtained through the combination of biological bone remodeling models with three distinct numerical techniques—finite element method (FEM), radial point interpolation method (RPIM), and natural neighbor radial point interpolation method (NNRPIM). A study combining these numerical techniques allows to compare their performance. Ultimately, this work supports the inclusion of meshless methods due to their smoother results and its easiness to be combined with medical images from CT scans and MRI. Abstract : This work performs a two‐dimensional spatiotemporal simulation of bone remodeling combining Komarova's model with distinct discretization methods: the finite element method (FEM), the radial point interpolation method (RPIM), and the natural neighbor RPIM (NNRPIM). Results support the inclusion of meshless methods in biological simulations, such as bone remodeling. Comparing the three numerical techniques, RPIM proves to be the most efficient approach when weighing the computational cost and the quality of results.